The impact of sociodemographic and clinical factors on adaptation to cancer among women with cervical cancer - Biber, Weronika; Ziemiańska, Joanna (Journal of Education, Health and Sport, 2026)
Introduction. Cervical cancer is a serious health, social, and economic problem. It belongs to the group of the most frequently diagnosed malignant neoplasms of the female reproductive system in Poland and worldwide. Adaptation to cancer, particularly in the case of cervical cancer, is a complex process that includes psychological, emotional, and social aspects. Aim. The aim of the study was to assess adaptation to cancer among patients with cervical cancer, taking into account sociodemographic and clinical factors. Material and Methods. The diagnostic survey method was used in this study. The research was conducted using an original questionnaire and the Mini-Mental Adjustment to Cancer Scale (Mini-MAC). The study included 65 patients diagnosed with cervical cancer who were treated surgically at the Oncology Outpatient Clinic and the Gynecology and Obstetrics Outpatient Clinic at the hospital in Żywiec. The respondents were informed in advance about the purpose of the study and that participation was voluntary and anonymous. The inclusion criteria were consent to participate in the study and a diagnosis of cervical cancer. Results. The study did not demonstrate statistically significant relationships regarding the impact of sociodemographic and clinical factors on adaptation to cancer. Conclusions. In the studied group of patients, the analyzed sociodemographic and clinical factors, including age, place of residence, marital status, financial status, level of education, type of occupation, and type of surgical procedure, did not affect adaptation to cancer.